Implementasi Pembelajaran IPAS Terintegrasi Keterampilan Abad 21 dalam Kurikulum Merdeka - Nikmah, Farikhatun; Muzdalifah, Muzdalifah; Retnanto, Agus (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
Changes in subjects in the independent curriculum in Elementary Schools (SD)/MI include science and social studies subjects becoming Natural and Social Sciences (IPAS). The aims of this research are to 1) Describe the implementation of science and science learning integrated with 21st century skills in the independent curriculum in class V MIN 2 Pati; 2) Describe the supporting and inhibiting factors in the implementation of integrated science and science learning with 21st century skills in the independent curriculum in class V MIN 2 Pati; 3) Describe the results of the implementation of integrated science and science learning for 21st century skills in the independent curriculum in class V MIN 2 Pati. The research method used is qualitative research with a case study approach. The results of the research found that Madrasah Ibtidaiyah Negeri (MIN) 2 Pati is one of the madrasas that has implemented an independent curriculum for 2 academic years. In implementing science and science learning in the independent curriculum, there are several steps, namely: learning planning, learning implementation and learning closure. In its implementation, it uses differentiation learning methods, PBL and inquiry. The media used in learning include pictures, LCD and projectors.